Effectiveness of Transactional Analysis Training on Cognitive Flexibility, Resilience and Anxiety in Mothers of Children with Externalized Behavioral Problems - Nejatifar, Sara; Fahami, Zahra; Abedi, Ahmad (Psychology of Woman Journal, 2022)
The purpose of this study was to investigate the effectiveness of transactional analysis training on cognitive flexibility, resilience and anxiety in mothers of children with externalized behavioral problems. The method of the present study was quasi-experimental with pre-test and post-test design and a control group. The statistical population of the present study included all mothers of children with externalized behavioral problems in Isfahan in 2021, 30 of whom were selected by available sampling and randomly divided into experimental and control groups. The experimental group received 120 minutes of transactional analysis intervention (Widdowson, 2014) during two months and 8 sessions, and the control group received no training. The data which collected through the Dennis & Vander Wal cognitive flexibility inventory, the Connor and Davidson resilience Questionnaire and the Spielberger state-trait anxiety inventory, were assessed by using analysis of covariance. The results show that transactional analysis intervention leading to improved cognitive flexibility and resilience and on the other hand reduced obvious anxiety. But this intervention did not have a significant effect on reducing mothers' latent anxiety. Therefore, according to the results of the study, it can be stated that attention to psychological problems of mothers of children with externalized behavioral problems is necessary and transactional analysis intervention can be used as an effective intervention in improving the problems of mothers of children with externalized behavioral problems.